2014
DOI: 10.1111/hsc.12130
|View full text |Cite
|
Sign up to set email alerts
|

Impediments to community-based care for people ageing with intellectual disability in rural New South Wales

Abstract: The emerging phenomenon of ageing with an intellectual disability has become subject to an increasing research focus in recent years. However, there remains little knowledge regarding the specific impediments that community workers face in supporting this cohort. The aims of the current study were to identify the major factors that, direct care staff believe, have most impact upon individuals ageing with an intellectual disability in the community. A three-round Delphi project was conducted across rural areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…8 It is further understood that there is a higher proportion of informal carers in rural localities compared to metropolitan locations, 11 and it is recognised that healthcare issues are potentially worse in country areas where access to healthcare services may be compromised. 28 The SF-36 Scale has been used in some Australian longitudinal studies such as the Household Income and Labour Dynamics Australia (HILDA), using a panel survey design, 44 and the Women's Health Australia (WHA) study. 45 However, the HILDA survey does not have a specific focus on information about caregiving issues and its impact on health, whereas the WHA is limited to women participants in specific age cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8 It is further understood that there is a higher proportion of informal carers in rural localities compared to metropolitan locations, 11 and it is recognised that healthcare issues are potentially worse in country areas where access to healthcare services may be compromised. 28 The SF-36 Scale has been used in some Australian longitudinal studies such as the Household Income and Labour Dynamics Australia (HILDA), using a panel survey design, 44 and the Women's Health Australia (WHA) study. 45 However, the HILDA survey does not have a specific focus on information about caregiving issues and its impact on health, whereas the WHA is limited to women participants in specific age cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…25 26 A failure to receive appropriate and timely treatment magnifies the issues for carers, as the existing health condition then worsens progressively over time, 27 which then places additional stress onto the carer. 28 Individuals in rural areas are less likely to receive formal carer training to cope with these concerns, 29 and this in turn can lead to issues with poor self-esteem. 30 In spite of these issues, there remains only limited research that specifically examines the issues and caregiver burden facing individuals in rural areas of Australia.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…As such, various chronological figures including 45, 50 and 60 have all been used in previous research to define when an individual may be considered ageing (Bigby, ). However, irrespective of the definition, it is known that as this cohort of the population ages, there is an increase in care needs (Haveman et al ., ), which can result in additional barriers to service access (Wark et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Bureaucratic and practice barriers have been identified that limit the rights of people with intellectual disabilities to access appropriate end‐of‐life support (Read & Todd, ; Todd, ; Wark, Hussain, & Edwards, ), and this is resulting in suboptimal care being provided to a highly vulnerable section of the community (Read, ). There is ongoing uncertainty across rural and metropolitan areas of Australia on how to best support individuals with intellectual disability during their end of life (Wark, Hussain, & Edwards, ; Wiese, Stancliffe, Balandin, Howarth, & Dew, ), both in terms of how and where such services should occur, and with respect to the intersection between disability providers and the mainstream and specialist health services (Wiese, Stancliffe, Dew, Balandin, & Howarth, ; Wiese, Stancliffe, Read, Jeltes, & Clayton, ).…”
Section: Introductionmentioning
confidence: 99%